The Effect of Zikir Therapy to Reduce Social Anxiety of Students in Islamic Boarding School - Arizona; Andika Ari Saputra; Fattah Hanurawan; Nur Hidayah; Muslihati; Mei Sarri; Nurkumalasari (Universitas Islam Negeri Madura, 2025)
This study aims to test the effectiveness of dhikr therapy in reducing social anxiety in students at Islamic boarding schools. Using an experimental design with an experimental group that underwent dhikr therapy and a control group that did not receive intervention, this study measured changes in social anxiety using the Liebowitz Social Anxiety Scale (LSAS) before and after the intervention. The results of the Wilcoxon analysis showed that the experimental group experienced a significant decrease in social anxiety with a Z value of -2.81 and p <0.05, while the control group did not show a significant change (Z = -0.577, p > 0.05). Dhikr therapy is effective in reducing social anxiety in students, both in terms of avoidance and anxiety. These results are in line with the theory of religious psychology and mindfulness, which shows that dhikr practices can calm the mind and increase emotional stability, helping individuals manage anxiety in social interactions. This study supports the application of dhikr therapy as an effective approach to reducing social anxiety in Islamic boarding schools.